The narcotraffic violence in the countries of greater coca production: The cases of Peru and Colombia - Cubides Salazar, Olga Marcela; Universidad Sergio Arboleda (Pontificia Universidad Javeriana, 2015)
This paper makes a comparison between the drug violence in Peru and Colombia. These two countries are the greater cocaine producers in the world, but present different levels of violence.In the case of Peru there are low levels of violence, whilst in the case of Colombia, the levels are high. The paper argues that the cocaincultivation and production in itself is not a source of high levels of violence. The intensity of the violence depends on the presence of other variables that will be proposed and analized here.